Analysis of Students' Numeracy Literacy Ability in Analyzing Graph and Table Information - Alyaro Nurhamida; Nego Linuhung; Rina Agustina (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
The ability to analyze information presented in graphs and tables is an important aspect of numeracy, as it is one of the indicators used to measure numeracy literacy internationally. This particular ability remains a challenge for students because it requires a high level of cognitive ability. However, it has not been extensively explored in depth. This study aimed to describe the difficulties encountered by tenth-grade senior high school students in analyzing information presented in the form of stacked bar charts and weekly expenditure tables. This study employed a descriptive qualitative approach. Initial data were collected through a numeracy literacy test consisting of one context-based problem involving a system of linear equations in three variables (SPLTV), which had been validated by an expert in mathematics education and used as an instrument for selecting the research subjects. The subjects were selected using purposive sampling. The selected subjects were then explored in greater depth through semi-structured interviews. The findings showed that, when analyzing information presented in graphs and tables, the participants experienced varying degrees of mathematical misunderstanding, ranging from a failure to coordinate the two representations, which resulted in strategic errors, to a gap between their understanding and their ability to solve mathematical problems. This study provides an empirical description of specific areas in which students experience difficulties with data-representation-based numeracy. The implication is that greater emphasis should be placed on instructional design that explicitly trains students to establish conceptual connections when solving problems